TCRβ repertoire of CD4+ and CD8+ T cells is distinct in richness, distribution, and CDR3 amino acid composition - Li, Hoi Ming; Hiroi, Toyoko; Zhang, Yongqing; Shi, Alvin; Chen, Guobing; De, Supriyo; Metter, E. Jeffrey; Wood, William H.; Sharov, Alexei; Milner, Joshua D.; Becker, Kevin G.; Zhan, Ming; et al. (Journal of leukocyte biology, 2016)
Distinct features of TCRβ repertoire present between CD4+ and CD8+ T cells could be used to evaluate the competency of the T cell immunity. The TCR repertoire serves as a reservoir of TCRs for recognizing all potential pathogens. Two major types of T cells, CD4+ and CD8+, that use the same genetic elements and process to generate a functional TCR differ in their recognition of peptide bound to MHC class II and I, respectively. However, it is currently unclear to what extent the TCR repertoire of CD4+ and CD8+ T cells is different. Here, we report a comparative analysis of the TCRβ repertoires of CD4+ and CD8+ T cells by use of a 5′ rapid amplification of cDNA ends–PCR–sequencing method. We found that TCRβ richness of CD4+ T cells ranges from 1.2 to 9.8 × 104 and is approximately 5 times greater, on average, than that of CD8+ T cells in each study subject. Furthermore, there was little overlap in TCRβ sequences between CD4+ (0.3%) and CD8+ (1.3%) T cells. Further analysis showed that CD4+ and CD8+ T cells exhibited distinct preferences for certain amino acids in the CDR3, and this was confirmed further by a support vector machine classifier, suggesting that there are distinct and discernible differences between TCRβ CDR3 in CD4+ and CD8+ T cells. Finally, we identified 5–12% of the unique TCRβs that share an identical CDR3 with different variable genes. Together, our findings reveal the distinct features of the TCRβ repertoire between CD4+ and CD8+ T cells and could potentially be used to evaluate the competency of T cell immunity.